Ketahanan Pangan Rumah Tangga Tani Lahan Kering di Kecamatan Jerowaru Kabupaten Lombok Timur - Wiriana, Wiriana; Hayati, Hayati; Sjah, Taslim (Universitas Mataram, 2024)
Food is a basic necessity that must be fulfilled daily, and its demand increases with population growth, making food security crucial. Farmer households in arid regions rely heavily on agriculture for income and food, but limited resources and climate change can affect their food security. This study aims to analyze the food security of dryland farming households in Jerowaru District, East Lombok Regency, using a quantitative descriptive method with primary and secondary data. A snowball sampling technique was used, involving 30 respondents. Data collection took place in November 2024, and Microsoft Excel was used for analysis. The study found that 28 (93.33%) farming families are food secure, while 2 (6.67%) are food insecure. Despite the high level of food security, the presence of food insecurity in some households highlights the need for local government intervention to prevent vulnerability among these farming families.